2004
DOI: 10.1051/medsci/2004206-7710
|View full text |Cite
|
Sign up to set email alerts
|

Le myocyte cardiaque adulte peut-il encore proliférer ?

Abstract: La croissance et la prolifération postnatale sont des caractéristiques essentielles des myocytes cardiaques qui permettent au coeur d'adapter progressivement sa masse à la demande hémodynamique. Mais, une fois l'âge adulte atteint, l'arrêt des divisions semble être un mal nécessaire au maintien de la stabilité des fonctions électriques et mécaniques du myocarde. Les myocytes cardiaques ont-ils toutefois gardé la capacité de proliférer ? La question est, pour plusieurs raisons, loin d'être académique. Ainsi, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Many studies have demonstrated that pesticides, including insecticides and herbicides, can induce oxidative stress, leading to alteration in lipid peroxidation, free-radical scavengers, and a series of antioxidants (Banerjee et al, 1999;Etemadi-Aleagha et al, 2002;Abdollahi et al, 2004). Additionally, some studies have shown that UGTs are involved in the detoxification processes, including that of drugs, pesticides, and endogenous compounds (Mazerska et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that pesticides, including insecticides and herbicides, can induce oxidative stress, leading to alteration in lipid peroxidation, free-radical scavengers, and a series of antioxidants (Banerjee et al, 1999;Etemadi-Aleagha et al, 2002;Abdollahi et al, 2004). Additionally, some studies have shown that UGTs are involved in the detoxification processes, including that of drugs, pesticides, and endogenous compounds (Mazerska et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 39 studies, including 7,914 patients, revealed the concordance rate between Pipelle and D&C/hysteroscopy/hysterectomy in endometrial cancer detection of postmenopausal and premenopausal women was 99.6% and 91%, respectively (32). However, the Pipelle is random point sampling and said to sample 4.2% of the uterine cavity (33), and 25–36% women using Pipelle were found to have insufficient tissue for pathologic assessment (34).…”
Section: Discussionmentioning
confidence: 99%